FORMATION OF SPINIFEX TEXTURE IN KOMATIITES: AN EXPERIMENTAL STUDY - Faure F.; Libourel G.; Arndt N. (My University, 2006)
The formation of platy olivine spinifex, the texture that characterizes komatiite lavas, has long been enigmatic. A major problem is that the dendritic morphology of the olivine resembles that of crystals grown in laboratory experiments at high cooling rates (>50°C/h), but at the position where these textures form, up to several meters below the komatiite flow top, the cooling rate cannot have been greater than 1-5°C/h. We performed experiments that demonstrate that the platy habit of spinifex olivine or pyroxene is a consequence of slow cooling of ultramafic magma in a thermal gradient (7-35°C/cm). The charges were cooled at rates between 2 and 1428°C/h and, even at the low cooling rates, the thermal gradient led to constrained growth and the development of preferentially oriented dendritic crystals with morphologies like those in natural platy spinifex-textured lavas. Under these conditions, olivine starts to crystallize at temperatures well below the equilibrium liquidus temperature (37°C < -ΔT < 56°C) depending on the composition of the starting material. When the cooling rate is high, the thermal gradient has a negligible effect on the texture and the crystals have a random orientation, like that in the upper parts of komatiite flows. © 2006 Oxford University Press.
Keywords: COOLING RATE; EXPERIMENTAL PETROLOGY; KOMATIITE; SPINIFEX; THERMAL GRADIENT